Helminth-derived proteins as immune system regulators: a systematic review of their promise in alleviating colitis - Alghanmi, Maimonah; Minshawi, Faisal; Altorki, Tarfa A.; Zawawi, Ayat; Alsaady, Isra; Naser, Abdallah Y; Alwafi, Hassan; Alsulami, Soa’ad M.; Azhari, Ala A.; Hashem, Anwar M; Alhabbab, Rowa (BMC immunology, 2024)
Helminth-derived proteins have immunomodulatory properties, influencing the host’s immune response as an adaptive strategy for helminth survival. Helminth-derived proteins modulate the immune response by inducing anti-inflammatory cytokines, promoting regulatory T-cell development, and ultimately favouring a Th2-biased immune response. This systematic review focused on helminth-derived proteins and explored their impact on reducing inflammatory responses in mouse models of colitis. A systematic search across Medline, EMBASE, Web of Science, and Cochrane Library identified fourteen relevant studies. These studies reported immunomodulatory changes, including increased production of anti-inflammatory cells and cytokines. In mouse models of colitis treated with on helminth-derived proteins, significant improvements in pathological parameters such as body weight, colon length, and microscopic inflammatory scores were observed compared to control groups. Moreover, helminth-derived proteins can enhance the function of Tregs and alleviate the severity of inflammatory conditions. The findings underscore the pivotal role of helminth-derived proteins in immunomodulation, specifically in the axis of cytokine secretion and immune cell polarization. The findings offer new opportunities for treating chronic inflammatory conditions such Crohn’s disease.